Mirages of Development Science and Technology for the Third Worlds - Salomon, Jean-Jacques (Lynne Rienner Publishers, 2023)
The authors consider why the great majority of Third World countries have failed to solve the problems of underdevelopment by relying on science and technology, while a very few of them-the newly industrialized countries-have at least partially succeeded